Aplikasi Sistem Informasi Smart Register Online Berbasis Android Menggunakan Algoritma Brute Force - Suprapto, Dimas Dandy Aryarajendra; Fauziah, Fauziah; Fitri, Iskandar; Hayati, Nur (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
The process of registering new students (PMB) for sharing information displayed on the website based PMB information system. However, constraints in the usage of the website are prospective students must monitor the website frequently to obtain information. If not accordingly a student is at risk of lagging behind the latest information. The research aims to expand a registration information system on the enrollment of student-based websites and developed into an Android-based application. So it is very easy for students to access PMB information, and registration through the Android application. This study designed an Android-based registration information system application using the waterfall method, brute force algorithm, integrated realtime firebase database and firebase storage cloud. The results of testing the brute force algorithm on the word search "S1 Informatics Engineering" with the input string "Informatics" carried out 8 steps of searching. These results by calculating the parameters of cyclomate complexity, region, and independent path from whitebox tests obtained the same results, the amount of 16. The results of testing blackbox method declared successful and as expected. So it can be concluded the development of an online smart register information applyÂ  the brute force algorithm is said to be feasible to implementation in the process of registering new students in accordance with the testing that has been done.